ANALISIS KEBUTUHAN GURU DALAM PENGEMBANGAN BUKU AJAR BERMUATAN KEARIFAN LOKAL PASCA PANDEMI CIVID-19 DI KABUPATEN KOTABARU - Muhammad Ali; Husni Mubarak; Usman DP (STKIP Paris Barantai, 2022)
The aims of this research to analysis needs in development of teaching materials containing local of wisdom that the appropriate with characteristic existing of students. The research is descriptive qualitative of research with using design the case study of the research. The research of sample 20 teacher to every school that are in Kabupaten Kotabaru. The technique of collecting data that used of questioner and the analysis needs in development of teaching materials containing local of wisdom and development based on the analysis of indicator. The data obtained and then the analysis using the descriptive based on the result of the total answer that giving the respondent. The result of analysis questioner needs and the result observation development of teaching book show that the teacher and students need textbooks containing post covid-19 local wisdom in Indonesia that are easy to understand, equipped with pictures that support of learning materials, containing the latest findings related to learning materials, and there is a glossary containing terms in the field of learning. Key words: Need analysis, teaching book, teacher needs.